Comparative Study Between Haemorrhage and Surgical Emphysema as Complication of Emergency Tracheostomy (Journal of Dhaka Medical College, 2021)
Background: Emergency tracheostomy is the commonest surgical intervention performed as lifesaving procedure by ENT surgeons on patients in emergency room of ENT and ICU. Several operative and postoperative complications have been reported after tracheostomy including fatal hemorrhage. Massive subcutaneous neck emphysema occurred because ventilation started at the time when the hemorrhage was not completely managed and the tracheal tube was not fully secured.Objective: This study was conducted to compare haemorrhage and surgical emphysema as complication of emergency tracheostomy among patients admitted in Department of ENT and Head-Neck Surgery in Dhaka Medical College & Hospital.Methods and Materials: This was a Cross Sectional Study conducted in the ENT and Head- Neck Surgery Department, Dhaka Medical College Hospital from July 2015 to June 2016. A total of 90 patients were included who fulfilled the selection criteria. Non probability convenient sampling was used to collect data. Statistical analysis was done by SPSS version 21.Results: Mean± SD of the study subjects was 49.84±17.4 years with most patients belonged to 40-79 years age group. 28.9% patients had habit of smoking and betel nut chewing. (48.9%) patients suffered from Ca larynx. Out of 90 tracheostomy patients, 40(44.4%) patients had had different complications including haemorrhage (13.3%), surgical emphysema (10%), haemorrhage with surgical emphysema (6.7%), tube blockage (3.3%), wound infection (3.3%) and injury to local tissue (2.2%). Haemorrhage occurs from anterior jugular vein, middle thyroid veins and thyroid gland and included peroperative haemorrhage (7.8%), immediate post- operative haemorrhage,